Analisis Potensi Bahaya Lingkungan Kerja Pada Nelayan Pesisir Tradisional - Karina Nasution, Priska; Hasibuan, Abdurrozzaq; Aulia, Shabina; Puspa Dewi, Virda (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
Fishermen are people whose lives depend directly on marine products, either by fishing or cultivation. They generally live on the beach, a residential neighborhood close to the location of their activities. This study aims to analyze the potential hazards of the work environment in traditional coastal fishermen. The research method used is library research or literature studies to obtain research data and use a qualitative approach generated in words or descriptions from books, and journals related to potential occupational environmental hazards in traditional shore fishermen. From the results of the study, it can be concluded that work as a fisherman is a profession that has a high risk to occupational safety and health. Dynamic work environments, such as the sea, make fishermen vulnerable to a variety of potential physical, chemical, biological, ergonomic, environmental, and psychosocial hazards.